Forgiveness Experiences in Early Adult Women with Divorced Parents - Anggraeni Rusmahadewi; Zufar Fadhlurrahman; Kartika Nur Fathiyah (Universitas Muhammadiyah Surakarta, 2024)
Divorce by parents can be a traumatic experience for children, especially women who are vulnerable to psychological problems in adulthood. A woman whose parents divorced and grew up in a broken home family must find a way to regulate and heal her emotional wounds. This research aims to explore the forgiveness experiences of early adult women with divorced parents. This research uses a qualitative approach with phenomenological methods. This research involved four participants with the following criteria: (1) women aged between 21-30 years, (2) have divorced parents, and (3) live in Yogyakarta which were obtained through social media broadcasts. The data collection was carried out using in-depth interviews. The research results found that the forgiveness experiences of early adult women can be grouped into two major themes, namely (1) the process of forgiving parents, which includes feelings, internal and external factors that encourage the forgiveness process as well as cognitive, emotional and behavioral aspects of forgiveness; and (2) the impact of forgiveness on participants' acceptance and meaning of their parent's divorce as well as participants' trust and hope in romantic relationships. This research offers supporting evidence that the process of forgiving in women with divorced parents can generate positive meaning and foster a sense of trust and hope in future romantic relationships. Furthermore, the results of this study can encourage mental health practitioners, especially in divorce cases, to consider handling relational aspects between children and parents in order to build trust and hope as a provision for their future romantic relationships.